2023
DOI: 10.24199/j.mmv.2023.82.05
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic status and distribution of Australian caddisflies (Insecta: Trichoptera)

Abstract: This review of the status of Australian caddisflies focuses on publications from 1982 to 2022. Information is provided on new species described in that period, new keys, new descriptions of both adults and larvae, and the distribution of families and genera from states/regions and the Northern Territory. Australia’s caddisfly fauna now totals 27 families, 111 genera and 868 species, with 97.9% of species endemic to Australia (only 19 of the 868 species are known from outside Australia, mainly from the nearby i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Investigation of the distributional range (especially inland extent) of common species in relatively undisturbed streams may make it easier to separate biogeographical and habitat-related distribution from changes due to human-induced degradation. Additionally, there are potentially more EPT species in south-western Australia that are only known by voucher specimens or are not represented in taxonomic keys (Cartwright et al, 2023;Dean, 1999a) -further taxonomic work and nymph descriptions could help clarify the true species richness and aid identification (Braby & Williams, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigation of the distributional range (especially inland extent) of common species in relatively undisturbed streams may make it easier to separate biogeographical and habitat-related distribution from changes due to human-induced degradation. Additionally, there are potentially more EPT species in south-western Australia that are only known by voucher specimens or are not represented in taxonomic keys (Cartwright et al, 2023;Dean, 1999a) -further taxonomic work and nymph descriptions could help clarify the true species richness and aid identification (Braby & Williams, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that EPT species richness and abundance were effective at distinguishing sites by degradation level. However, Newfoundland has up to 165 EPT taxa (Lomond, 1997), substantially higher than the estimated total across south-western Australia of 67 (Cartwright et al, 2023;Dean, 1999aDean, , 2000Hynes & Bunn, 1984;Sutcliffe, 2003;Suter, 1999;Webb & Suter, 2011).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations